Format of Options in a Multiple Choice Test Vis-a-Vis Test Performance - Hermabeth O. Bendulo; Erlinda D Tibus; Rhodora A Bande; Voltaire Q Oyzon; Myrna L Macalinao; Norberto E Milla (International Journal of Evaluation and Research in Education (IJERE), 2017)
Testing or evaluation in an educational context is primarily used to measure or evaluate and authenticate the academic readiness, learning advancement, acquisition of skills, or instructional needs of learners. This study tried to determine whether the varied combinations of arrangements of options and letter cases in a Multiple-Choice Test (MCT) affect the test performance of the homogenous BEED students. A test was designed and administered to test the performance across test items employing different arrangement of options (Cascading, Inverted N, Z eye movement, and One-line Horizontal) and across case of letter options (upper and lower case), that is, a total of eight (8) treatments. The statistical analyses revealed that there is an insignificant difference in the mean performance of students in relation to letter cases and arrangement of letter choices in a multiple choice test. Thus, the test performance of students in a multiple choice type of test does not depend on either letter cases or arrangement of letter choices.